Nível de conhecimento dos cirurgiões dentistas sobre a qualidade dos prontuários odontológicos para fins de identificação humana - Silva, Alessandro A. L.; França, Diurianne Caroline Campos [UNESP]; Aguiar, Sandra Maria Herondina Coelho Ávila de [UNESP]; Spadácio, Célio; Daruge Junior, Eduardo (My University, 2011)
Objective: The aim of this research was to determine the knowledge level of 400 dentists registered in the Regional Dental Council of Cuiabá, through a questionnaire about the importance of records in the process of human identification. Results: We observed that 48.36% of them dispense between 10 and 20 minutes. Only 13.1% of the surveyed dentists did not have the habit of writing down the oral conditions of their patients before starting treatment and 42.62% have only one odontogram filled. From the 122 participants, 11.11% reported that the documentation had no utility to establish the patients identity. To make the situation worse, 33.6% of them said they did not keep the records of patients updated. Conclusion: We conclude that the dentist of Cuiabá has enough knowledge on preparing, maintaining and importance of dental records before the death in the identification process for establishing the patient identity. But, always he did not properly fills the dental records, thus it has been reducing their clinical, administrative and legal value.

Objetivo: O objetivo desta pesquisa foi determinar por meio de questionário a 400 cirurgiões-dentistas cadastrados no Conselho Regional de Odontologia de Cuiabá-MT, o nível de conhecimento dos mesmos sobre a importância do prontuário nos processos de identificação humana. Resultados: Observou-se que 48,36% dos respondentes dispensam entre 10 e 20 minutos. Apenas 13,1% dos cirurgiões-dentistas pesquisados não têm o hábito de anotar as condições bucais antes de iniciar o tratamento e 42,62% fazem somente um odontograma. Dos 122 participantes, 11,11% informaram que a documentação não teve utilidade para estabelecer a identidade. Agravando o quadro, 33,6% dos respondentes afirmaram que não mantém os prontuários de pacientes atualizados. Conclusão: Concluiu-se que o cirurgião-dentista de Cuiabá-MT apresenta conhecimento satisfatório sobre elaboração, manutenção e importância do prontu- ário odontológico antes da morte no processo de identificação para o estabelecimento da identidade do paciente. Porém, nem sempre o preenche adequadamente, reduzindo assim o seu valor clínico, administrativo e legal.
Level of knowledge of dentists on the quality of dental records for human identification
Keywords: Forensic anthropology; Forensic dentistry; Clinical record; Legal liability; Antropologia forense; Odontologia legal; Ficha clínica; Responsabilidade legal